1965
DOI: 10.1302/0301-620x.47b2.283
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Fracture of the First Rib

Abstract: 1. Two cases of bilateral fracture of the first rib are reported. The fractures were situated near the neck of the first rib. 2. A possible mechanism responsible for the bilateral fracture of the first rib at this particular site has been suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This produces a bending strain resulting in a fracture just behind the attachment of the scalene medius muscle. A similar probable mechanism was suggested by Joshi SG et al 15 5 patients were injured due to a fall on an outstretched hand (4 from RTA and 1 from height) resulting in fracture at shaft of first rib on the same side. This was probably due to strong violent contraction of the scalenus anterior muscle combined with traction on the arm.…”
Section: Discussionsupporting
confidence: 63%
“…This produces a bending strain resulting in a fracture just behind the attachment of the scalene medius muscle. A similar probable mechanism was suggested by Joshi SG et al 15 5 patients were injured due to a fall on an outstretched hand (4 from RTA and 1 from height) resulting in fracture at shaft of first rib on the same side. This was probably due to strong violent contraction of the scalenus anterior muscle combined with traction on the arm.…”
Section: Discussionsupporting
confidence: 63%
“…This is attributed to the unique anatomical characteristic of the first rib. The first rib is a deeply seated structure shielded by the shoulder girdle and its surrounding muscles [3]. Thus first rib fractures (unilateral) are classically caused by high energy trauma resulting in serious damage to mediastinal structures, rupture of the subclavian vessels and trauma to the brachial plexus and minor damage to the clavicle and scapula (as illustrated by the second patient) [2,4].…”
Section: Discussionmentioning
confidence: 99%
“…Indirect injuries have been attributed to violent contractions of juxtacostal muscles such as the scalene and sternocleidomastoid muscles which result in severe bending strain at a relative point of weakness at the first rib such as the subclavian groove [3].…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism is said to be elicited by a sudden unexpected hyperextension of the cervical spine (Joshi et al 1965, Frangakis 1967 ) independent follow-up study of stress fractures which revealed spontaneous bony union and which could not be taken to mean that this was a developmental anomaly.…”
Section: Discussionmentioning
confidence: 98%
“…Isolated fracture of the first rib often occurs without a history of trauma (Alderson 1947), or after a trauma which is rarely linked to the fracture. Therefore, the mechanism of this fracture has been discussed by many authors in the past (Jones 1869, Aitken & Lincoln 1939, Proctor et al 1945, Brook 1959, Joshi et al 1965, Frangakis 1967, Blichert-Toft & Nielsen 1968, Guillermand 1971. Some authors have even doubted the existence of such a fracture, interpreting the finding instead as a developmental anomaly (Bowie & Jacobson 1945).…”
mentioning
confidence: 99%